A Visual Assay of a Loop-Mediated Isothermal Amplification Based Vertical Immunoassay for SARS-CoV-2 RNA Detection - Yu, Mengtao; Huang, Pei; Li, Yuanguo; Song, Yumeng; Liu, Xingqi; Feng, Na; Jin, Hongli; Bai, Yujie; Zhang, Haili; Li, Yuanyuan; Xia, Xianzhu; Gao, Yuwei; et al. (Frontiers in Microbiology, 2022)
SARS-CoV-2 is a novel coronavirus that has caused a global pandemic. To date, 504,907,616 people have been infected and developed coronavirus disease 2019 (COVID-19). A rapid and simple diagnostic method is needed to control this pandemic. In this paper, a visual nucleic acid detection method combining reverse transcription loop-mediated isothermal amplification and a vertical flow visualization strip (RT-LAMP-VF) was successfully established and could detect 20 copies/μl of SARS-CoV-2 RNA within 50 min at 61 °C. This assay had no cross-reactivity with a variety of coronaviruses, including SARSr-CoV, MERS-CoV, OC43, 229E, HKU1, and HKU4, exhibiting very high levels of diagnostic sensitivity and specificity. Most strikingly, this method can be used for detecting multiple SARS-CoV-2 variants, including the Wuhan-Hu-1 strain, Delta and Omicron variants. Compared with the real-time RT–PCR method recommended by the World Health Organization (WHO), RT-LAMP-VF does not require special equipment and is easy to perform. As a result, it is more suitable for rapid screening of suspected SARS-CoV-2 samples in the field and in local laboratories.